2014
DOI: 10.1002/cmmi.1584
|View full text |Cite
|
Sign up to set email alerts
|

Molecular magnetic resonance probe targeting VEGF165: preparation and in vitro and in vivo evaluation

Abstract: A new method for imaging the tumor human vascular endothelial growth factor 165 (VEGF 165) is presented. A magnetic resonance imaging (MRI) probe was prepared by crosslinking ultrasmall superparamagnetic iron oxide (USPIO) nanoparticles to the aptamer for tumor vascular endothelial growth factor 165 (VEGF165-aptamer). The molecular probe was evaluated for its in vitro and in vivo activities toward VEGF165. Enzyme-linked immunosorbent assay showed that the VEGF165-aptamer-USPIO nanoparticles conjugate specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…18 Recently, an aptamer coupled with USPIO was fabricated to target vascular endothelial growth factor 165 overexpressed by some tumors. 19 However, till now, reports on the application of aptamer-based MR probes specific for HCC are lacking. In this study, we successfully developed a novel HCC-targeted MR probe by conjugating GPC3-specific aptamer with USPIO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Recently, an aptamer coupled with USPIO was fabricated to target vascular endothelial growth factor 165 overexpressed by some tumors. 19 However, till now, reports on the application of aptamer-based MR probes specific for HCC are lacking. In this study, we successfully developed a novel HCC-targeted MR probe by conjugating GPC3-specific aptamer with USPIO.…”
Section: Discussionmentioning
confidence: 99%
“…17 Recently, studies have shown the efficacy of aptamer-iron oxide probes for in vivo tumor-targeted MRI. 18,19 However, to the best of our knowledge, an aptamer-based MR probe specific for HCC has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…These iron/protein nanocontainers inherently home to cancer cells that overexpress the transferrin receptor 1 (TfR1). Finally, it should be noted that DNA and RNA aptamers have been widely used to engineer MNPs for specific molecular recognition …”
Section: Surface Engineering Of Mnpsmentioning
confidence: 99%
“…Thus, an aptamer targeting VEGF165 was chemically linked with ultrasmall super paramagnetic iron oxide (USPIO) nanoparticles. This VEGF165-aptamer-USPIO enhanced the contrast of T2-weighted imaging in the liver cancer of mice xenografts (Figure 2) [117]. …”
Section: Aptamer-based Diagnosismentioning
confidence: 99%
“…Arrows point to tumor xenografts. Reprinted from [117] with permission from John Wiley and Sons, copyright 2014.…”
Section: Aptamer-based Diagnosismentioning
confidence: 99%